Evaluation the effect of dietary vitamin E, sesamin and thymoquinone bioactive compounds on immunological response, intestinal traits and MUC-2 gene expression in broiler Japanese quails (Coturnix japonica) - Yaser Rahimian; Farshid Kheiri; Mostafa Faghani (Animal Biotechnology, 2024)
The current study was performed to determine the effect of dietary vitamin E, sesamin and thymoquinone bioactive lignans derived from sesame and black seed on immunological response, intestinal traits and Mucin2 gene expression in broiler quails. Three hundred and fifty (one days-old) quails were allotted to seven dietary treatments with five replicates as an experimental randomized design study. Treatments were basal diet as a control, control +100 and +200 mg of vitamin E, sesamin and thymoquinone per each kg of diet respectively. At 35 d of age, two quails from each pen were chosen, weighted, slaughtered, eviscerated and lymphoid organ relative weights were measured. Anti-body titers against Newcastle disease (ND), Sheep red blood cell (SRBC), and infectious bronchitis virus (IBV) and Avian influenza (AI) vaccination were determined. The serum activities of alkaline phosphatase (ALP), alanine aminotransferase (ALT), aspartate aminotransferase (AST) and serum antioxidant activates such as superoxide dismutase (SOD),glutathione peroxidase(GPX), catalase (CAT) and total antioxidant capacity (TAC) were examined. The cell mediated immunity by dinitrochlorobenzene (DNCB) and phytohemagglutinin (PHA) challenges were assessed. The microflora populations of ileum, morphological traits of jejunum and mucin2 gene expression were analyzed. Data showed that the lymphoid organ (thymus, spleen and Bursa) relative weights and antibody titer against HI, AI, SRBC and IB vaccination were increased compared to the control (p ≤ 0.05). Serum activities of ALP, ALT and AST were decreased under influences of dietary treatments (p ≤ 0.05). The serum antioxidant activates of GPX,SOD,CAT and TAC were increased and Increasing in mean skin thickness after DNCB challenge and decrease wing web swelling response to PHA mitojen injection were observed (p ≤ 0.05). Salmonella enterica, E-coli and Coliforms colonies were decrease and Lactobacillus colonies increased instead (p ≤ 0.05). The villus height and surface, crypt depth and goblet cells density were increased compared to the control (p ≤ 0.05). The expression of MUC2 gene increased under influnces of vitamin E, sesamin and thymoquinone supplemented diets (p ≤ 0.05).